Extended mixed vector equilibrium problems - Rahaman, Mijanur; Kilicman, Adem; Ahmad, Rais (Hindawi Publishing Corporation, 2014)
We study extended mixed vector equilibrium problems, namely, extended weak mixed vector equilibrium problem and extended strong mixed vector equilibrium problem in Hausdorff topological vector spaces. Using generalized KKM-Fan theorem (Ben-El-Mechaiekh et al.; 2005), some existence results for both problems are proved in noncompact domain.